The weakest link: A novel use of network analysis for the broken passing links in football - Mclean, S.; Salmon, P. M. (Science and Medicine in Football, 2019)
Background: Understanding passing connectivity in football is a critical component of team performance assessment. Many studies have examined successful passing via network analysis; however, no research has attempted to understand the broken passing connections as a network in football. Method: In a first of its kind study, we assessed a teams` unsuccessful or `broken` passing links using network analysis. The analysis used the 2018 UEFA Champions League final between Real Madrid and Liverpool. The broken passing links were identified and analysed using network analysis to determine team and individual network characteristics. Results: Eventual winners Real Madrid had fewer players involved in the broken passing links network, compared to Liverpool. The analysis also highlights the individual contributions, in terms of passers and intended recipients within the broken passing links network. Discussion: This short communication study has demonstrated a novel use of network analysis to analyse the broken passing networks in football. This extension to the utility of network analysis in football could be used as a tool for coaches and match analysts to understand team and opposition performance. Further research is recommended to test the method across multiple games, levels of competition, and pitch location, of the broken passing links.